Anemia in patients with inflammatory bowel disease as a risk factor for restless legs syndrome. Literature review - S. A. Zakharova; A. L. Kalinkin (Нервно-мышечные болезни)
Restless legs syndrome (RLS) is a neurological, sensorimotor disorder. It is characterized by the uncomfortable and unpleasant sensations in the legs which begin or worsen during periods of rest, primarily in the evening or night, and are relieved by movement. Central iron deficiency plays a vital role in the pathogenesis of RLS. There is evidence that chronic inflammation is an additional risk factor for RLS. Anemia is the most common complication and extraintestinal manifestation of inflammatory bowel disease, therefore the prevalence of RLS in these patients is a problem of great interest. In addition, inflammatory bowel disease patients’ sleep disturbances directly influence the disease’s clinical course and can be the preclinical marker of exacerbation. It is essential for clinicians to be aware of RLS as a possible reason for sleep disturbance and as a factor that negatively affects the quality of life in inflammatory bowel disease patients.